Effect of Temperature on Microstructure and Texture Development in A7075 Aluminum Alloy Subjected to Biaxial Alternate Forging - So, Tae-Yeong; Kim, Nam-Seok; Shin, Young-Chul; Cho, Chang-Hee (Archives of Metallurgy and Materials, 2026)
In this study, the microstructural evolution of an A7075 aluminum alloy subjected to severe deformation by biaxial alternate forging (BAF) was investigated at room temperature (RT) and 300°C. SEM-BSE observations revealed no significant differences in the morphology or distribution of second-phase particles between the two conditions, indicating that deformation temperature did not markedly affect particle fragmentation at the applied strain level. However, SEM-EDS analysis of the matrix showed a noticeable reduction in Zn content after deformation at 300°C compared to RT, suggesting enhanced solute redistribution during high-temperature deformation. EBSD analyses demonstrated clear differences in deformation microstructures depending on both temperature and strain localization. At RT, the high-deformation region exhibited pronounced lattice distortion and heterogeneous orientation gradients, whereas deformation at 300°C resulted in more uniform IQ contrast and reduced intragranular misorientation, indicative of active recovery. Texture analysis based on ODF sections and pole figures showed moderate development of shear and rolling texture components, with more continuous and stabilized texture features at 300°C. These results indicate that elevated-temperature BAF promotes solute redistribution and recovery-assisted plastic flow without significant alteration of second-phase characteristics.